Blindness Disparities Between Racial/Ethnic Groups in the State of Texas - Angelica Garcia; Kent Anderson; Megan Funkhouser (University Library System, University of Pittsburgh, 2024)
Background: There are disparities in health outcomes between races. Blindness is associated with decreased quality of life and negative health outcomes. There is little published data investigating the difference in the prevalence of blindness between races/ethnicities nationally and in Texas. Methods: This retrospective observational study investigates the differences in crude prevalence of blindness between different race/ethnicities in Texas. Data was gathered from the Centers for Disease Control and Prevention (CDC) website Vision and Eye Health Surveillance System (VEHSS) using the most recently available Compositive Estimate data from the state of Texas. The variables compared were age groups and race/ethnicity categories of Black, non-Hispanic, Hispanic, any race and White, non-Hispanic, referred to as "Black," "Hispanic," and "White" respectively. The logs of the relative ratios and Z scores were used to compare each age group. Results: The Black group consistently had the highest crude prevalence of blindness across age groups; The White group had the lowest prevalence. The Hispanic group consistently had prevalence rates that were between the Black and White groups. No differences were found to be statistically significant. Conclusion: This data shows that, despite ongoing diversity and inclusion efforts, ongoing inequalities exist in healthcare outcomes. In the state of Texas, this is made apparent by the difference in blindness prevalence between Black, Hispanic, and White populations. These data can be used to bring about change that needs to be addressed at the state and institutional level.